Complete Ureteral Duplication: Outcome of Different Surgical Approaches - Rodrigues, Isabel (2016)
Introduction: The surgical management of complete ureteral duplication anomalies is not consensual.Objective: To characterize the pediatric population who underwent surgery for complete ureteral duplication and assess the outcomes of different approaches.Material and Methods: Clinical records from patients treated between January 2008 and June 2014 were retrospectively reviewed. Epidemiology, diagnosis, clinical manifestations and surgical procedures were collected and analysed. Ureteral units were divided into two groups: A, with ureterocele; and B, without it.Results: Forty-one ureteral units from 32 patients with complete duplication underwent surgery. In group A (n = 18), the selected primary procedure was: ureterocele punction (12); ureter reimplantation (3); pyelopyelostomy (2); heminephrectomy (1). A reintervention was required in 3 of the 12 units submitted to punction: heminephrectomy (1), ureteroureterostomy (1), and ureteric reimplantation (1). In group B (n = 23), STING was performed in 10 units, ureteric reimplantation in 3, pyelopyelostomy in 3, ureteroureterostomy in 1, and heminephrectomy in 6; two cases required reintervention. Discussion: A conservative primary approach was favoured in cases with ureterocele and/or reflux in hemisystems worth preserving (53.7%); it was effective per se in 75% (n = 9/12) units in group A and 80% (n = 8/10) in group B. An ablative primary procedure was adopted in 17% (n = 7/41) cases, 5.6% of group A (n = 1/18) and 26.1% of group B (n = 6/23).Conclusions: A conservative approach is effective as a primary and isolated procedure in the majority of cases with ureterocele or vesicoureteral reflux. Further studies are needed to establish the advantages over primary invasive or ablative approaches.